2016
DOI: 10.1007/s10811-015-0786-z
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics and inferred changes in thylakoid membrane fluidity determine bloom succession between Anabaena and Microcystis in eutrophic lakes

Abstract: Anabaena and Microcystis are common dominant cyanobacterial genera and frequently form blooms in large shallow eutrophic lakes in China. There is usually a quick succession between these two cyanobacterial blooms in early summer; however, there is currently no solid evidence based on photosynthesis and population competition to explain this phenomenon. This study compared the photosynthetic parameters and the indirectly measured thylakoid membrane fluidity characteristics between Anabaena and Microcystis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…In this study, the TLP was down-regulated in the diseased seedlings. Evidences showed that the reduction of TLP not only damaged the thylakoid electron flow, but also decreased chlorophyll a content and further slacked the photosynthesis (Wang et al, 2016 ; Zhu, 2016 ), this result is consistent with the previous RNA-seq results, which showed that a reduction in photosynthesis of phytoplasma-infected plants could be attributed to the loss of several thylakoid membrane proteins (Mou et al, 2013 ). At the same time, the expression of LHCI was reduced, which severely affected the light reactions in Photosystem I (PSI) (Bressan et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the TLP was down-regulated in the diseased seedlings. Evidences showed that the reduction of TLP not only damaged the thylakoid electron flow, but also decreased chlorophyll a content and further slacked the photosynthesis (Wang et al, 2016 ; Zhu, 2016 ), this result is consistent with the previous RNA-seq results, which showed that a reduction in photosynthesis of phytoplasma-infected plants could be attributed to the loss of several thylakoid membrane proteins (Mou et al, 2013 ). At the same time, the expression of LHCI was reduced, which severely affected the light reactions in Photosystem I (PSI) (Bressan et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…To avoid light limitation and the interactive effects between P availability and irradiance, we chose a suitable irradiance of 30 μmol photons m –2 s –1 for D. flos-aquae according to the suggestion from the FACHB-collection and our previous experience with this genus . In light of our results, we predict that the paradigm of N loading reduction stimulating N 2 -fixing cyanobacterial blooms occurs only when P loading is high.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cells deficient in ribosomal proteins and slower proliferating, have been shown to be eliminated by neighboring faster proliferating cells in the Drosophila wing (26). This phenomenon can also be observed in the interaction between species, applicable to cohabiting plants or microbes (27,28). Formulas of species interaction have been used to determine the dynamics of species proliferation in a cohabiting milieu.…”
Section: Discussionmentioning
confidence: 99%